Erythrocyte levels in chronic obstructive pulmonary disease (COPD) patients with a history of positive and negative COVID-19 - Siti Nur Chasanah; Aslani Thereestiana Sari; Djamila Zakaria; Ayutia Safira Rusidana Thalib (Acta Biochimica Indonesiana, 2025)
Background: Chronic obstructive pulmonary disease (COPD) is a prevalent respiratory condition that predisposes patients to severe complications when infected with SARS-CoV-2 (COVID-19). Hematological alterations, particularly in erythrocyte levels, may influence the clinical course and outcomes in these high-risk individuals. Objective: This study aimed to evaluate the erythrocyte profile of COPD patients with and without COVID-19 at RS Paru Dr. Ario Wirawan Salatiga. Methods: An analytic study design was employed. Participants were recruited using consecutive sampling. All COPD patients admitted between March 2019 and December 2023 were included. A total of 53 COPD patients participated, comprising 27 COVID-19-positive and 26 COVID-19-negative patients. Results: The mean erythrocyte level in the COVID-19-positive COPD group was 4.23 ± 0.73 million/µl, while in the COVID-19-negative COPD group, it was 4.77 ± 0.78 million/µl. Although a statistically significant difference was observed between the two groups (p = 0.012), both values remain within the normal reference range. Conclusion: Erythrocyte levels in both the COVID-19-positive and COVID-19-negative COPD groups remained within the normal range, although the levels were relatively lower in the COVID-19-positive group with statistical significance. Further research is needed to explore the underlying mechanisms contributing to this difference.